Microbiological quality of honey market in North-Centre of Rio de Janeiro - Pereira, Ingrid Annes; Teixeira, Francisco Martins; Finger, Regina Maria; Souza, Mariana de Azevedo (Revista de Ciências Agroveterinárias, 2024)
The present work aimed to diagnose honey microbiological profile of samples obtained in the Center-North region of Rio de Janeiro, Brazil. A total of 25 honey samples were analyzed for: counts of total and thermotolerant coliforms, filamentous fungi and yeasts, Staphylococcus spp., Clostridium spp. and Bacillus spp. and detection of Salmonella spp. The results of microbiological analyzes detected the most significant presence of filamentous fungi and yeasts, mesophilic bacteria, Bacillus cereus and Staphylococcus spp. Although the majority of honey samples presented positive isolations for microbiological markers, the counting results were in accordance with the limits established by national legislation. Only three (12%, 3/25) honey samples presented counts above the recommended limit for filamentous fungi, yeasts and mesophilic bacteria, reflecting an unsatisfactory hygienic-sanitary pattern for consumption. The detection of these microbiological markers in honey samples sold in the Center-North region of Rio de Janeiro points to the strengthening of public policies to support beekeeping and food safety.